A Chromatic Aberration-Measuring Method for Refracted Converging Lens based on Foucault Knife - Edge Test - Nguyen, Thanh Dong; Vu, Toan Thang (Old Journal, 2017)
The paper proposes a new chromatic-aberration-measuring method for geometric optics of a single converging lens based on the Foucault knife-edge test. An opto-mechatronics measurement system aided by a computer vision was built to automatically determine displaced positions of the knife-edge for discovering chromatic aberration components in the measured lenses. The evaluation results of its chromatic aberration elements measured by this system are appropriated with theoretical calculations.